2020
DOI: 10.1109/tia.2020.2986325
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Optimal Design for Net Zero Energy Houses Including Hybrid Electric and Thermal Energy Storage

Abstract: Net zero energy (NZE) houses purchase zero net metered electricity from the grid over a year. Technical challenges brought forth by NZE homes are related to the intermittent nature of solar generation, and are due to the fact that peak solar generation and load are not coincident. This leads to a large rate of change of load, and in case of high PV penetration communities, often requires the installation of gas power plants to service this variability. This paper proposes a hybrid energy storage system includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…3. INSPIRE+D incorporates freeware such as Energy-Plus, BEopt, OpenDSS, and Python, and is capable of both power flow analysis at the system level, and house energy modeling along with HEM at the single house level [29]. Its scalability allows the simulation of thousands of different house models in parallel, utilizing a high-performance computing (HPC) system with thousands of cores.…”
Section: Technology Demonstrator and Analysis Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…3. INSPIRE+D incorporates freeware such as Energy-Plus, BEopt, OpenDSS, and Python, and is capable of both power flow analysis at the system level, and house energy modeling along with HEM at the single house level [29]. Its scalability allows the simulation of thousands of different house models in parallel, utilizing a high-performance computing (HPC) system with thousands of cores.…”
Section: Technology Demonstrator and Analysis Frameworkmentioning
confidence: 99%
“…Most EWH manufacturers provide the CTA-2045 modules in their new products or offer refurbishments to enable real-time communication and control [27], [28]. Previous research published by the extended group of authors showed that a smart home may achieve comparable functionality with a smaller battery energy capacity, provided that special EWH and associated controls are incorporated in a hybrid energy storage system [29]. The paper included a systematic sizing procedure for such a home-based hybrid energy storage system and modeled it with a co-simulation framework for building energy use and electric power flow in distribution systems.…”
Section: Introductionmentioning
confidence: 99%
“…The technical and economic constraints of different energy services, which might serve for net-zero emissions energy systems have been presented in [11]. On a smaller scale, the concept of net-zero energy buildings has been analyzed [12]. The technologies, construction design, and their operation have been presented in [13] and [14].…”
Section: Introductionmentioning
confidence: 99%
“…As PV penetration keeps rising, there are multiple benefits of incorporating EWHs into home energy management. Recent research indicates that battery capacity may be reduced by up to 30% when batteries are coordinated with EHW, which were regarded as "uni-directional" energy storage [2].…”
Section: Introductionmentioning
confidence: 99%